Study on the minimum quality requirements for dual career services (European Union, 2016)
This is the final report on the "Study on Minimum Quality Requirements for Dual Career services". Between March and November this year, the Amsterdam University of Applied Sciences (AUAS) has conducted this study together with Birch Consultants, the Talented Athlete Scholarship Scheme (TASS - England), the European Athletes as Students (EAS) network, and the Free University of Brussels (VUB). The study has delivered a set of 25 country profiles in which existing Dual Career policies and programmes at national and regional level are specified per country. Additionally, the study has resulted in the development of an "athlete-centred" quality framework in which all levels of influence (from personal, to institutional, to policy level) are addressed. Also, we have drafted a preliminary checklist of minimum requirements for high performance training centres, which could function as a reference point for the establishment of international high performance training centres. We conclude with a strong recommendation to focus on a monitoring tool and (self) assessment of Member States with regard to their policies and programmes for effectively combining Dual Career. In doing so, it is our aim to make sure that the current estimated 120.000 athletes per year can successfully combine education, training or work with sport to enable each athlete to reach full potential in life. (Source: Original abstract)